STRUCTURAL AND FUNCTIONAL CHANGES OF THE HEART IN COAL INDUSTRY WORKERS - Коротенко, Ольга Юрьевна; Панев, Николай Иванович; Филимонов, Егор Сергеевич; Панев, Роман Николаевич (Medicine in Kuzbass, 2021)
Subject of research. There were examined 1118 workers in the coal industry. 369 miners were examined as a part of the periodic medical examination, 657 miners with dust-causing lung pathology were examined in hospital as well as 92 miners without dust-causing lung pathology aged 40-55 years. Objective of research was to study the structural and functional changes in the heart of workers in the coal industry. Methods of research. All patients underwent an echocardiographic study according to standard methods with an assessment of the left ventricular deformity, an ultrasound study of the main arteries and a study of respiratory function, there was calculated the Quetelet index, smoker’s index, measured the waist and hip circumferences, and studied the lipid profile and glycated hemoglobin in blood serum. Main results. It was revealed that when dust-causing lung pathology was combined with coronary heart disease, eccentric remodeling of the left ventricle and concentric remodeling of the right ventricle were noted. When dust-causing lung pathology was combined with arterial hypertension, as well as with ischemic heart disease and arterial hypertension – a concentric remodeling of the left and right ventricles might occur. Miners with dust-causing lung pathology in combination with cardiovascular disease showed a more pronounced impairment of filling in both left and right ventricles. The antiorthostatic test revealed early signs of the right ventricular diastolic dysfunction. There was a decrease in longitudinal deformity of the left ventricle and preclinical signs of diastolic dysfunction of the right ventricle in coal industry workers without cardiovascular pathology, Conclusion. Coal industry workers, with long-term work experience in hazardous underground working conditions in the absence of somatic and occupational pathology, develop preclinical left ventricular systolic dysfunction and right ventricular diastolic dysfunction. Dust-causing lung pathology leads to structural and functional changes in the heart, which are aggravated by concomitant cardiovascular pathology.